SIGNIFIKANSI PENELITIAN TINDAKAN KELAS BAGI GURU DALAM PROSES PEMBELAJARAN DI SMPN 8 TENGGARONG - Romeli, Ahmad; Kholis, Nur; Riadi, Akhmad (AZKIYA, 2023)
Classroom Action Research (CAR) is a strategic approach that helps teachers improve the quality of learning through a cycle of planning, implementation, observation, and reflection. This article aims to explore the significance of Classroom Action Research (CAR) for teachers in the learning process at SMPN 8 Tenggarong, focusing on benefits, challenges, and optimization strategies. The research uses a descriptive qualitative method with literature review as the main approach. The study results indicate that PTK has a positive impact, such as improving teachers' pedagogical skills, encouraging learning innovations, and enhancing students' learning outcomes. However, the main challenges faced include time constraints, high administrative burdens, and a lack of training on the implementation of PTK. To overcome these challenges, strategies such as intensive training, collaboration among teachers, and administrative support from the school are needed. In conclusion, PTK has significant importance in improving the quality of learning and the professionalism of teachers at SMPN 8 Tenggarong. With the optimization of PTK implementation, it is hoped that learning will become more effective, innovative, and relevant to students' needs.